Developing Students’ Reading Comprehension Abilities Using the Reading Workshop Learning Model in Students of Class IV of State Elementary Number 101992 Cimahi - Sitepu, Darmainur; Sutikno, Sutikno (PT Inovasi Pratama Internasional, 2025)
The reading ability of elementary school students in Indonesia remains low, particularly at Public Elementary School Number 101992, Cimahi, Bangun Purba District. This study aims to identify factors contributing to low reading ability and to evaluate the effectiveness of the Reading Workshop model in improving students’ reading comprehension skills. The research questions focus on (a) students' initial and final reading abilities using the Reading Workshop model, (b) the model's effectiveness in enhancing reading skills, (c) significant differences in students' reading abilities before and after implementation, and (d) the strengths and weaknesses of the model. This study employed a quasi-experimental method with a one-group pretest-posttest design. Data were collected through tests, questionnaires, and observations. The study was conducted in Class IV of Public Elementary School Number 101992. The findings reveal a significant improvement in students' reading comprehension, as indicated by the statistical result t count (2.78) > t table (2.66) at p < 0.05 with df = 58. This suggests that the Reading Workshop model is effective in enhancing reading skills among elementary students. The study highlights the potential of structured reading interventions to address literacy challenges and improve students' academic performance.